2009
DOI: 10.1021/bi900149f
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the PLP Degradative Enzyme 2-Methyl-3-hydroxypyridine-5-carboxylic Acid Oxygenase from Mesorhizobium loti MAFF303099 and Its Mechanistic Implications

Abstract: A vitamin B6 degradative pathway has recently been identified and characterized in Mesorhizobium loti MAFF303099. One of the enzymes on this pathway, 2-methyl-3-hydroxypyridine-5-carboxylic acid oxygenase (MHPCO), is a flavin-dependent enzyme and catalyzes the oxidative ring opening of 2-methyl-3-hydroxypyridine-5-carboxylic acid to form E-2-acetaminomethylene succinate. The gene for this enzyme has been cloned and the corresponding protein has been overexpressed in Escherichia coli and purified. The crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…In the case of ring opening of pyridines, these compounds are rare but have been observed in microbial metabolism reported by Kaiser et al (1996), Chaiyen et al (1997), andMcCulloch et al (2009). For example, 2-methyl-3-hydroxypyridine-5-carboxylic acid oxygenase was identified to be involved in the degradation of vitamin B 6 in bacteria and catalyzed oxidative ring opening of 2-methyl-3-hydroxypyridine-5-carboxylic acid to form E-2-acetaminomethylene succinate (Chaiyen et al, 1997;McCulloch et al, 2009). In addition to oxidative ring opening of hydroxylated pyridines, pyridine ring opening has also been proposed via reduction followed by ring fission under anaerobic conditions by Kaiser et al (1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ring opening of pyridines, these compounds are rare but have been observed in microbial metabolism reported by Kaiser et al (1996), Chaiyen et al (1997), andMcCulloch et al (2009). For example, 2-methyl-3-hydroxypyridine-5-carboxylic acid oxygenase was identified to be involved in the degradation of vitamin B 6 in bacteria and catalyzed oxidative ring opening of 2-methyl-3-hydroxypyridine-5-carboxylic acid to form E-2-acetaminomethylene succinate (Chaiyen et al, 1997;McCulloch et al, 2009). In addition to oxidative ring opening of hydroxylated pyridines, pyridine ring opening has also been proposed via reduction followed by ring fission under anaerobic conditions by Kaiser et al (1996).…”
Section: Discussionmentioning
confidence: 99%
“…[57] The structure of MHPCO from Mesorhizobium lofi MAFF303099 and the mechanism of the enzyme from Pseudomonas MA1 have been studied in quite some detail. [30,58,59] The overall MHPCO structure resembles that of PHBH, but the flavin occupies the in conformation in both free and substrate bound structures. Interestingly, the active site is larger than that in PHBH and contains nine water molecules deputized to form most of the bonds with the substrate.…”
Section: Mhpco: Unusual Pyridine Ring-opening Reactionmentioning
confidence: 99%
“…Structural and rapid kinetics studies on wild-type and engineered enzyme variants elucidated many details of the catalytic cycle of PHBH. Moreover, these investigations revealed that the isoalloxazine ring of the FAD cofactor is mobile and can swing in and out of [19,20] A 1PN0; 1FOH phenol 2-monooxygenase (PHHY) [22,23] A 2DKH; 2DKI 3-hydroxybenzoate 4-hydroxylase (MHBH) [24] A 2 A1; 2 A2 UW16 12-hydroxylase (PgaE/CabE) [25] A 2R0C; 2R0G; 2R0P 7-carboxy-K252c hydroxylase (RebC) [26] A 2VOU 2,6-dihydroxypyridine 3-hydroxylase (DHP) [27] A 2RGJ phenazine-1-carboxylate hydroxylase (PhzS) [28] A 3IHG aklavinone 11-hydroxylase (RdmE) [29] A 3GMB; 3GMC 2-methyl-3-hydroxypyridine-5-carboxylic acid oxygenase (MHPCO) [30] E 3IHM styrene monooxygenase (StyA) [9] Scheme 1. Reactions catalyzed by (A) PHBH, (B) PHHY, (C) MHBH, (D) DHP hydroxylase.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports on metabolism of pyridine include N-oxidation, N-methylation (Damani et al, 1986), and N-glucronidation (Lin, 1999;Wiener et al, 2004). On the other hand, few cases of ring opening of pyridine have been reported, including microbial ring opening of pyridine derivatives (Kaiser et al, 1996), the formation of muconaldehyde from benzene mediated by cytochrome P450 (Latriano et al, 1986), and the formation of E-2-(acetaminomethylene) succinate from a vitamin B6 degradant (McCulloch et al, 2009). It is noteworthy that there are reports, albeit rare, on other six-membered aromatic heterocyclic ring-opening biotransformation, such as pyrimidine ring-cleaved metabolites of PF-00734200, a dipeptidyl peptidase inhibitor (Sharma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%